Allergies: diseases closely related to cancer - Belén Tirado-Rodríguez; Sara Huerta-Yépez (Permanyer, 2016)
Allergies are hypersensitivity reactions that occur through specific type Th2 immunological mechanisms characterized by different soluble mediators, as well as specific cells of the immune system. In recent decades, evidence has emerged relating this disease with cancer development. However, most of the results of epidemiology studies have been controversial and contradictory. There are mainly two trends. While the first indicates that allergies can reduce the risk of cancer, the other indicates that they may increase this risk. The first trend can be explained by the immunosurveillance hypothesis, which states that the increased immune surveillance after the immune hyper-responsiveness can inhibit or exert a protective effect against the development of cancer. Similarly, the prophylaxis hypothesis suggests that the physical effects of allergy symptoms can prevent cancer by removing potential carcinogens. In contrast, the opposing hypothesis propose that there is a deviation of the immune response toward Th2, which favors the development of cancer, or that the process of chronic inflammation favors the generation of mutations, and therefore the development of cancer. With the purpose of understanding more about these two hypotheses, the main soluble and cellular factors of allergic diseases that could be playing a key role in the development or inhibition of cancer were considered in this review.